POLICY ANALYSIS OF THE AJATAPPARENG TECHNICAL IMPLEMENTING UNIT (UPT) ON THE REHABILITATION OF PROTECTED FOREST AND LAND (RHL) BY PT INHUTANI IN PUJANANTING VILLAGE PUJANANTING DISTRICT BARRU DISTRICT - A.Aminah; A.Ariyadi; Linda (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal